Notes on the discourses around the Colombian-Ecuadorian border - Espinosa, Roque (2016)
This article analyses the on-going imaginaries about the Northern border which stem from the current discourses produced by the Ecuadorian legal, political and military establishments. Within the narratives constructed by these dis-courses, borders are seen as places in which disorder rules, as regions where democracy is not well established, and as areas which are prone to become war scenarios. Since the late 1980s, these imaginaries have been portraying borders as places of insecurity. According to the author, these discourses reproduce common-sense statements, which do not allow a full comprension of the situations and conditions lived by border societies.